Assistance Of Farmers In Utilizing The Consortium Of Endophite Bacteria And Organic Fertilizer As Well Organic Pesticides Based On Local Wisdom To Increase Rice Productivity - Aziez, Achmad Fatchul; Wiyono; Budiyono, Agus (Universitas Tunas Pembangunan Surakarta, 2023)
The